Tigecycline-resistant Escherichia coli ST761 carrying tet(X4) in a pig farm, China - Wang, Jing; Lu, Meng-Jun; Wang, Zhen-Yu; Jiang, Yue; Wu, Han; Pan, Zhi-Ming; Jiao, Xinan (Frontiers in Microbiology, 2022)
This study aimed to investigate the prevalence and characterization of tet(X4) in Escherichia coli isolates from a pig farm in Shanghai, China, and to elucidate tet(X4) dissemination mechanism in this swine farm. Forty-nine (80.33%) E. coli strains were isolated from 61 samples from a pig farm and were screened for the presence of tet(X). Among them, six (12.24%) strains were positive for tet(X4) and exhibited resistance to tigecycline (MIC≥16 mg/L). They were further sequenced by Illumina Hiseq. Six tet(X4)-positive strains belonged to ST761 with identical resistance genes, resistance profiles, plasmid replicons, and cgMLST type except that additional ColE10 plasmid was present in isolate SH21PTE35. Isolate SH21PTE31, as a representative ST761 E. coli strain, was further sequenced using Nanopore MinION. The tet(X4) in SH21PTE31 was located on IncFIA18/IncFIB(K)/IncX1 hybrid plasmid pYUSHP31-1, highly similar to other tet(X4)-carrying IncFIA18/IncFIB(K)/IncX1 plasmids from ST761 E. coli and other E. coli lineages in China. These IncFIA18/IncFIB(K)/IncX1 plasmids shared closely related multidrug resistance regions, and could reorganize, acquire or lose resistance modules mediated by mobile elements such as ISCR2 and IS26. Phylogenetic analysis were performed including all tet(X4)-positive isolates obtained in this pig farm combined with 43 tet(X4)-positive E. coli from pigs, cow, pork, wastewater, and patients with the same ST from NCBI. The 50 tet(X4)-carrying E. coli ST761 isolates from different areas in China shared a close phylogenetic relationship (0-49 SNPs). In conclusion, clonal transmission of tet(X4)-positive E. coli ST761 has occurred in this swine farm. E. coli ST761 has the potential to become a high-risk clone for tet(X4) dissemination in China.